2.PHAGE COCKTAILS AGAINST HIGHLY MULTI-DRUG RESISTANT ACINETOBACTER BAUMANII (Iraqi Journal of Medical Sciences, 2019)
Background:Phage therapy is a potential alternative treatment for infections caused by many bacterial species such as Acinetobacter baumannii (A. baumannii), a significant nosocomial pathogen, has evolved resistance to almost all conventional antimicrobial drugs in poor hygiene and conflicts areas like Iraq.Objective:Isolate and apply bacteriophages as alternative therapeutic agents against extensively drug-resistant (XDR) and pan-drug-resistant A. baumannii and evaluation extracted native endolysin activity.Methods:Twenty-three bacterial samples were collected in Al-Imamein Al-kadhimein Medical City hospital. Phages were isolated from different regions in Baghdad city including (soil, sewage, irrigation channels). Native endolysin was extracted from highly lytic phage that produced halo-like appearance around inhibition zone.Results:Out of 50 isolates, 23 isolates (46%) of XDR, pan-drug resistant (PDR) A. baumanii have been isolated from patients with various infections. 136 lytic phages specific to A. baumanii were isolated. Each bacterial isolate was sensitive to at least one lytic phage. Phage cocktails were formulated and were shown remarkably minimize the bacterial resistance to individual lytic phages. In addition, the endolysin native activity of lytic phages specific to A. baumanii evaluated in this study revealed a potent antibacterial activity (> 1 log) reduction of bacterial density in just one hour of endolysin treatment. Conclusion: Phage therapy assessed in this study was shown ability to efficiently solve the problems of “superbug” bacteria by lysing effectively most XDR, PDR bacteria in vitro. And, phage cocktails were shown to be superior over single-phage preparations in treating A. baumanii with much less resistance rate to therapeutic phages. Furthermore, intrinsic activity of native endolysin revealed promising results to tackling superbug pathogens.Keywords: Phage, Phage cocktails, Acinetobacter, native endolysin, extensively drug-resistant (XDR), and pan-drug resistant (PDR)Citation: Jasim HN, Abdul-Ameer AS. Phage cocktails against highly multi-drug resistant Acinetobacter baumanii. Iraqi JMS. 2018; 16(4): 357-371. doi: 10.22578/IJMS.16.4.2
Keywords: Phage; Phage cocktails; Acinetobacter; native endolysin; extensively drugresistant XDR; and pandrug resistant PDR